Construct Validity of the Movement Assessment Battery for Children-Second Edition Test in Preschool Children with Respect to Age and Gender - Kokštejn, Jakub; Musálek, Martin; Tufano, James J. (Frontiers in Pediatrics, 2018)
Abstract Background: The Movement Assessment Battery for Children-second edition (MABC-2) Age Band 1 is widely used to identify preschoolers with motor difficulties. Despite unsatisfactory construct validity of the original three-factor model MABC-2 (manual dexterity, aiming and catching, and balance), previous research has not considered possible age and gender differences throughout the entire preschool period. Aim: The aim of this study was to verify the construct validity of the MABC-2 Age Band 1 in a population of Czech preschoolers with respect to age and gender. Methods: Using data from 510 Czech preschoolers (3 to 6 years; 4.9±1.1 years), confirmatory factor analyses (CFA) were used for each age category and gender. Results: The goodness-of-fit indices of CFA supported the original three-factor model of the MABC-2 only in 3- and 4-year-old children, and in boys (3 to 6 years). Low factor loadings and ceiling effects of several test items (Drawing Trail, Walking Heels Raised, and Jumping on Mats) seem to be a probable cause of weak fit indices in 5- and 6-year-old children and in girls (3 to 6 years). Conclusions: These results suggest that the MABC-2 can be a valid tool for assessing motor development and identifying motor difficulties among 3- to 4-year-olds, and generally fits better for preschool boys in the Czech Republic. However, in 5- to 6-year-olds, ceiling effects and a low power of discrimination was found for the Drawing Trail, Walking Heels Raised, and Jumping on Mats tests. Therefore, the three-factor model is not appropriate for all preschoolers, and separate norms should be established for each age and gender.